2010
DOI: 10.1007/s11705-010-0521-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Cu/ZnO/Al2O3 catalyst under microwave irradiation for slurry methanol synthesis

Abstract: Cu/ZnO/Al 2 O 3 catalysts with Cu/Zn/Al ratios of 6/3/1 were precipitated and aged by conventional and microwave heating methods and tested in the slurry phase reactor for methanol synthesis. The effect of technological condition of precipitation and aging process under microwave irradiation on the catalytic performance was investigated to optimize the preparing condition of Cu/ ZnO/Al 2 O 3 catalyst. The results showed that the microwave irradiation during precipitation process could improve the activity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Acid sites of a catalyst are known to have an important role in the esterification reaction. According to the results of XRD analysis, the 0.4ZCA catalyst showed broad peaks with low intensity compared to the other samples, confirming good dispersion of copper and zinc oxides on alumina and an intense interaction, resulting in higher catalytic activity [39]. The 0.4ZCA catalyst showed maximum catalytic activity with relatively low water solubility.…”
Section: Acid Strength Acidity Activity and Reusability Of The Catamentioning
confidence: 92%
“…Acid sites of a catalyst are known to have an important role in the esterification reaction. According to the results of XRD analysis, the 0.4ZCA catalyst showed broad peaks with low intensity compared to the other samples, confirming good dispersion of copper and zinc oxides on alumina and an intense interaction, resulting in higher catalytic activity [39]. The 0.4ZCA catalyst showed maximum catalytic activity with relatively low water solubility.…”
Section: Acid Strength Acidity Activity and Reusability Of The Catamentioning
confidence: 92%
“…According to the study, the best catalytic performance was obtained when the precursors were precipitated at the pH of 6 to 8 at 70 °C followed by an aging time of 20–60 min and a final calcination at 300 °C. Fan et al 143 reported the assistance of microwave (MW) irradiation in the coprecipitation and in the aging steps for the synthesis of Cu–ZnO–Al 2 O 3 catalysts. Their results on one hand showed that MW irradiation at the coprecipitation step could improve the activity of the catalyst, but not the stability.…”
Section: Direct Hydrogenation Of Co 2 To Methanol mentioning
confidence: 99%
“…Also, the effect of microwave irradiation on the properties of CuO-ZnO catalyst prepared by coprecipitation method was studied. [29] It is well known that the properties of CuO-ZnO catalyst obtained by coprecipitation method are affected by various parameters. The interrelationships and interactions between the all parameters are complex, and the comprehensive analysis of this system to optimize the factors requires a time and laborconsuming work.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…These factors are calcination temperature (A), capping agent (B), drying temperature (C), precipitating agent (D), molarities of Cu and Zn ions (E), microwave power (F), and pH at the end of precipitation (G). In this study, experimental design was performed according to the L 8 (2 7 ) Taguchi orthogonal design [29,30] for optimizing the procedure to synthesis CuO-ZnO nanocomposite with high specific surface area. The seven factors and their levels are summarized in Table 1.…”
Section: Experimental Designmentioning
confidence: 99%